(3JGQjN GdOhd hGdedhcs - (3GHf GdaQGJ , eMeO Hf YHO GdQMje Hf Ydj Hf eMeO, fGUQ GdOjf GdMfaj,J (B807 (3g` s
(3ChdgG (B:s
(3jHJOF HhajGJ SfI (B531 s
(3BNQgG (B:s
(3jfJgi Edi MhGOK SfI (B543 s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdQGHYs
(3HChdg agQS HNW GdYdGeI JjehQHGTG cJGHI GdagQS HjVGA hcJGHg GdeLdO ShOGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B200 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B159s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B50 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B12 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B3197) s
Keywords: (3GdJGQjNs